Vision in Disbelief : The 4th Biennale of Sydney. - The 4th Biennale of Sydney, 1982 (Sydney : Biennale of Sydney, 1982)
Adams, Mac ; Ahearn, John ; Allen, Terry ; Apple, Billy ; Auerbach, Frank ; Ball, Sydney ; Baselitz, Georg ; Benedit, Luis F. ; Blume, Bernhard Johannes ; Brown, Bill ; Brus, Gunter ; Chia, Sandro ; Clemente, Francesco ; Cucchi, Enzo ; Eno, Brian ; Frank, Dale ; Genral Idea ; etc.
Vision in Disbelief : The 4th Biennale of Sydney, 7th April - 23rd May 1982, Painting, Sculpture, Photography, Installation: Art Gallery of New South Wales, Sydney ; Power Gallery of Contemporary Art, University of Sydney ; Ivan Dougherty Gallery, City Art Institute ; Australian Centre for Photography and Gallery A Courtyard space ; Roslyn Oxley Gallery - Performance, Film & Video, Sound: New South Wales Institute of Technology ; Cellblock Theatre East Sydney Technical College ; New South Wales Conservatorium of Music, 1982
English
kunstcatalogus